Utilization of Lesser-Used Timber Species in Clustered Furniture Industries of Ethiopia - Gemechu Kaba; Omer Hinde; Getachew Desalegn; Azmera Belachew; Saifu Amanuel; Eyuel Girmay; Mahadi Mussa; Asfaw Gelan (CV. Literasi Indonesia, 2022)
Demand for all forest products has been increasing in Ethiopia, due to population, economic growth, and the rise in the construction sector. In the past, about 85% of this demand has been covered by indigenous timber species which are now endangered and protected from harvest. As an alternative, there are potential lesser-used timber species in the country that can be utilized to narrow down the gap between supply and demand. This study aims to describe the utilization practices of timber species and identify factors affecting the utilization of lesser-used timber species in furniture industries. The study was conducted in four (4) purposively selected towns based on their Wood business transaction and resource availability. Both quantitative and qualitative data were collected using semi-structured questionnaires. A binary logit model was employed to estimate factors influencing the utilization of lesser-used timber species for industrial application. The results show that the majority of wood furniture industries still depend on pit sawed valuable indigenous timber species of the country. The result indicated that Cordia africana is the main type of timber species preferred to be utilized in the majority of furniture industries. It also indicated that there is a negative perception towards lesser-used timber species, less access to appropriate information, and skill training on wood processing. Therefore, the study implicates the need to intervene in changing perceptions toward these species and build the technical capacity of the wood industries through skill training.